Wernicke's encephalopathy in hyperemesis gravidarum: A systematic review. (May 2019) - Oudman, Erik; Wijnia, Jan W.; Oey, Misha; van Dam, Mirjam; Painter, Rebecca C.; Postma, Albert
Abstract: Pregnant women have an increased demand for thiamine. In hyperemesis gravidarum (HG) thiamine rapidly depletes, which can lead to Wernicke's Encephalopathy (WE). Our objective was to systematically review the signs and symptoms of WE in HG. We conducted our search from inception using Mesh terms hyperemesis, Wernicke Encephalopathy, Korsakoff's syndrome, and pregnancy. We searched Pubmed, Embase, Cochrane, Web of Science, Psychinfo, PiCarta, and Cinahl. We defined WE as mental, oculomotor, and motoric alterations and thiamine deficiency; HG was defined as severe nausea, and vomiting during pregnancy; adequate WE treatment as >500 mg/day intramuscular or intravenous. Our search yielded 146 case studies reporting on 177 cases. Pregnant WE patients became thiamine depleted between 10–15 weeks of gestation. Patients had been vomiting for a median of 7 weeks before WE, and had lost 12.1 kg. Prodromal signs of WE were nausea and vomiting (100%), double vision (37.4%), and blurred vision (27.4%). Treatment with subtherapeutic thiamin dose was common (63.6%), WE was exacerbated by intravenous glucose administration (14.1%). We found chronic cognitive disorders occurred in 65.4%, pregnancy loss in 50%, and maternal death in 5% of cases. Thiamine supplementation was insufficient or absent from treatment plans. To eradicate WE in pregnancy, it is necessary to give 100 mg of intravenous or intramuscular thiamine in HG patients with persistent or severe late onset vomiting to prevent them from developing WE.